AN EVALUATION OF PROMOTING AND DEVELOPING PENCAK SILAT SKILLS PROJECT TO THE EXCELLENCE OF STUDENTS IN SOMDETPITTAYAKOM SCHOOL - Saenkanya, Phumsak (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of the research article were 1) to evaluate context, input, process, and product of an evaluation of promoting and developing Pencak Silat skills project to the excellence, 2) to study the guidelines in promoting and developing Pencak Silat skills project to the excellence. The purposive samples were 98 students studying in Sports: 42 of mathayomsuksa 4, 36 of mathayomsuksa 5, and 20 of mathayomsuksa 6. There were 6 key informants consisted of school director, vice directors, and person in charge of the project. The instruments used to collect data included questionnaire, interview form, and focus group questions. The statistics used to analyze the data were frequency, percentage, mean, standard deviation, and content analysis. The results revealed as follows: 1) An evaluation of context, input, process, and product of promoting and developing Pencak Silat skills project to the excellence. 1.1) Having evaluated the context, the objectives of the project in accordance with Ministry of Education policy was at the highest level.1.2) Having evaluated the input, knowledge and competence in the project management of a person in charge of the project was at the highest level. 1.3) Having evaluated the process, the counseling care of a person in charge of the project was at the highest level. 1.4) Having evaluated the product, knowledge, and competence in the project management of administrators was at the highest level. 2) Guidelines for promoting and developing Pencak Silat skills project to the excellence. 2.1) The curriculum of the project was appropriate. 2.2) Teachers or a person in charge of the project possessed knowledge and competence in the project management, and Pencak Silat skills. They could pass on knowledge to students. In addition, they had a network and partnerships to create opportunities for students in illustrating their potential. 2.3) The project duration was in 20 weeks of learning management in a semester. It took 60 minutes in each learning time. Furthermore, students must learn contents as well as skills over time. For instance, they learned after school and weekends. 2.4) The practice field was appropriate. 2.5) The teaching aids and facilities were adequate and appropriate.